Efeito da cafeína sobre a qualidade de ovos e desempenho de galinhas poedeiras - Mailson da Silva Teixeira (2019)
The objective of this study was to evaluate the effect of different concentrations of pure caffeine added to the diet of laying hens aged 56 to 68 weeks. A total of 576 chickens from the commercial Lohmann® LSL strain were used, distributed in a completely randomized design. The treatments consisted of three doses in the diet (150 ppm, 300 ppm, and 450 ppm) and one group without addition of caffeine (control), totaling four treatments with six replicates per treatment. During the twelve experimental weeks, several productive aspects of the birds were evaluated, such as feed intake, daily egg production, percentage of production, egg weight, bark quality and bark resistance parameters force required for breaking/drilling. The thickness of the bark was measured in three different points and the mean was obtained, and the dosages of calcium and phosphorus present in egg shells and histopathological evaluation of the whole oviduct were performed. There was a reduction in feed consumption by chickens, probably due to interference in the palatability of the food. As a consequence of the lower consumption of feed by birds, the egg production decreased and the shell structure was reduced to its resistance force, thus harming the qualitative standards of the eggs. The consumption of the highest concentration of caffeine in the diet (450 ppm of food) promoted a significant increase in the mortality of the chicken. On the other hand, it was found that up to 150 ppm of caffeine in the food (equivalent to the use of 40 kg per tonne of coffee husk in the diet) did not cause significant changes in egg quality and did not interfere with the health and performance of eggs. In the histological examination of the oviduct, infiltration by mononuclear inflammatory cells was observed. It was concluded that it is feasible to use caffeine-containing sources in the diet of laying hens with a concentration of up to 150 ppm of caffeine in the diet.